Understanding taxpayer's compliance on E-Commerce - Wiwit Irawati; Rendy Rendy; Dila Angraini; Dea Annisa; Tri Utami (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2021)
E-Commerce should be a potential source of tax revenue seeing its rapid growth and is supported by the growing growth of internet users. But in fact, the tax revenue target has not been achieved. This study aims to determine the effect of Taxpayer awareness and Understanding on Taxpayer compliance. The population used is taxpayers who do E-Commerce registered in Depok City, West Java. The sample was selected using a convenience sampling method with a sample size following the Slovin formula. Before testing the hypothesis, the data are tested by the validity and reliability test and the classical assumption test. The test results show that the understanding of tax regulations partially affects Taxpayer compliance. Furthermore, Taxpayer awareness has no partial effect on Taxpayer compliance with e-Commerce users.